Health camps in schools and content analysis of the school textbooks: A cross-sectional study in Tamil Nadu - P R Geetha Priya; Sharath Asokan; D Kandaswamy; S Malliga; G Arthi (Wolters Kluwer Medknow Publications, 2016)
Background: School textbooks have been considered as an effective platform for promoting oral health. The information on oral health in the Indian school textbooks has not been evaluated. Aim: The aim of this study was to evaluate the contents of school textbooks on oral health and to quantitatively analyze the school health camps and guest lectures/demonstrations conducted in the schools of three districts in Tamil Nadu. Methodology: Twenty schools which participated in the study followed the Central Board of Secondary Education, matriculation, or the state board syllabus. A questionnaire was designed to collect information about the medical camps, dental camps, guest lectures, and demonstrations conducted in the last academic year from the schools. The questionnaires were distributed among the school teachers of grades I-V. They were asked to provide photocopies of the topics on oral health which were included in the syllabus. Content analysis of the information on oral health-related topics in the school textbooks was done. Descriptive statistics of the details of the camps and lectures was done using Pearson's Chi-square test (SPSS version 17) (SPSS Inc. Chicago, Illinois, USA). Results: There was no significant difference in the number of medical camps (P = 0.445), dental camps (P = 0.055), and guest lectures (P = 0.069) organized among the three boards of schools. Basic information on the parts and type of teeth, tooth decay, and brushing were present in the textbooks of all three boards of schools. Conclusion: The school textbooks of all the three boards contained basic and adequate information on oral health. Periodic revisions of the content and quality of information in the school textbooks are essential. To make the information sticky for long-term, reinforcements in the form of school health education is needed.